2013
DOI: 10.1007/s12020-013-0091-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk and metabolic syndrome in primary hyperparathyroidism and their correlation to different clinical forms

Abstract: Cardiometabolic disorders have been associated with primary hyperparathyroidism (PHPT), while the relationship of cardiovascular risk score (CRS) and metabolic syndrome (MS) with different clinical presentation of PHPT remains undefined. Our aim was to evaluate CRS, MS and its components in PHPT looking for their correlation to different clinical forms. In 68 consecutive PHPT patients and 68 matched controls, CRS, MS and its components were assessed to perform an observational case-control study at an ambulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 35 publications
3
27
0
16
Order By: Relevance
“…Moreover, both BMI and the presence of a low-risk asymptomatic PHPT disease predicted MS after adjusting for age and sex (50). In PHPT patients with MS, Delfini et al showed higher mean values of leptin and lower adiponectin serum level compared to controls (78); these findings are interesting because an interaction between adipokines and bone metabolism has been recently suggested in the general population (79).…”
Section: Metabolic Syndromementioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, both BMI and the presence of a low-risk asymptomatic PHPT disease predicted MS after adjusting for age and sex (50). In PHPT patients with MS, Delfini et al showed higher mean values of leptin and lower adiponectin serum level compared to controls (78); these findings are interesting because an interaction between adipokines and bone metabolism has been recently suggested in the general population (79).…”
Section: Metabolic Syndromementioning
confidence: 92%
“…The high prevalence of type 2 diabetes mellitus in patients with PHPT was not confirmed in a large cohort of patients, even though the prevalence was still high in a subgroup of older patients and in men (47); differences are probably due to the retrospective nature of the investigation and the lack of appropriate controls (47). More subtle alterations of glucose metabolism, such as glucose intolerance and insulin resistance, have also been described in PHPT patient compared to controls by some (48,49,50), but not by all authors (35). The exact mechanism underlying this association is still unclear.…”
Section: Glucose Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Tassone et al (1) suggested that this was caused by significantly higher age of the patients with asymptomatic PHPT included in their study group when compared to symptomatic group (p<0.008). In a study by Procopio et al (8), 68 patients with PHPT and a control group were evaluated in 2013 with regard to the NCEP-ATP III MetS criteria and the prevalence of MetS was detected to be significantly higher in patients with PHPT than in controls (p<0.02). This higher prevalence was more prominent among patients with asymptomatic PHPT.…”
Section: Discussionmentioning
confidence: 99%
“…Increased PTH seemed to produce smaller ejection fraction and distension of the left ventricle. Smaller studies had the same results [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 90%